Identification of differentially expressed genes by nonradioactive differential display of messenger RNA - Bosch, Thomas C. G.; Lohmann, Jan U. (RNA Isolation and Characterization Protocols, 1998)
Changes in cell behavior are driven by changes in gene expression. Thus, in order to understand the mechanisms regulating cell behavior, one has to identify and characterize differentially expressed genes. Standard methods currently used to isolate differentially expressed genes include subtractive hybridization (1,2), differential hybridization (3), and single-cell polymerase chain reaction (PCR) (4). Differential display of mRNA by PCR (DD-PCR) is a new and powerful procedure for quantitative detection of dtfferentially expressed genes (5,6). Advantages over alternative approaches include: quantitative identification of differences in gene expression between different cell fractions; simultaneous detection of both upregulation and downregulation of genes; requirement of only small amounts of messenger RNA; and drastically reduced time of analysis. Since on average there are about 15,000 individual mRNA species present in any individual cell, some steps of selection have to be taken before the transcript population can be displayed simultaneously. Therefore, in the DD-PCR procedure mRNA from different cell fractions are reverse transcribed (RT) using an oligo-dT-NN anchor primer. Since this 3′ primer will hybridize only with transcripts carrying the corresponding two NN-bases in front of the poly(A) tail, only 1/12 (i.e., about 1200) of all transcripts are reverse transcribed into cDNA. Accordingly, for reverse transcription of all messages 12 different 3′ primer have to be used independently. PCR of the resulting cDNA is then carried out using radiolabeled dNTPs, the oligo-dT-NN anchor primer as 3′ primer and a short arbitrary oligonucleotide as 5′ primer. By using Homers as 5′ primers, about 150-300 products will be obtained in a PCR using 1200 different cDNAs as templates. Thus, for quantitative screening of the transcript pool of a particular cell, 20 arbitrary 5′ primers have to be used in 240 independent PCR reactions. After electrophoretrc separation of the resulting fragments on a polyacrylamrde gel, differentral gene expression is visualized by autoradiography. Differentially expressed cDNA species can be recovered from the gel using the autoradrogram for band localization DD-PCR has prevlously been employed to identify differentially expressed genes in preim-plantation mouse embryo (7), in human endothelial cells treated with fibroblast growth factor (8), in normal and tumor cells (9), and in Salmonella treated with peroxide (10). A recent review of the DD-PCR method can be found in McClelland et al. (6).
Gesehen am 26.01.2017